Investigation of TLP behavior under tendon damage. (15th May 2018) - Tabeshpour, Mohammad Reza; Ahmadi, Ali; Malayjerdi, Ebrahim
Abstract: Exact calculation of stiffness matrix of TLP is important for investigation of its behavior in intact and tendon damage conditions and it is necessary to design a reliable TLP. A serious attention has been concentrated on this problem in API-RP-2T and various aspects of that such as dynamic and static behavior of TLP, tendon tensions after one tether failure. Also it has introduced safety factors in different loads and healthy conditions. This paper deals with effect of damage tendon condition of TLP on behavior and tensions of tendons in wave frequency range. Equilibrium of TLP is studied and stiffness matrix of TLP is derived in tendon damage condition. Wave loads and hydrodynamic coefficients are calculated by boundary element method. Then, motion equations are solved for 48 load and healthy conditions and wave frequency portion of tensions and motions are extracted from time history of them. It is shown that although damage tendon condition has no extreme influence on response amplitude magnification, it has a relatively major effect on tension of tendons which are close to failed tendon. In addition, roll and pitch magnifications have major effect on increase in tension of tendons. Also, it is seen that critical wave heading occurs in direction of diagonal of group of failed tendon. Highlights: Roll and pitch motions are the most important ones that affect tendon tensions of TLP. Magnification of them is most important in change of tensions of tendons. it can be deduced since Tension RAO is similar to pitch or roll. One can say that pitch and roll are critical motions in investigation of tendon tensions in tendon failure scenarios. Critical heading in this condition is in direction of diagonal of failed tendon.